Analysis and design of analog integrated circuits - Gray, Paul R.; Hurst, Paul James; Lewis, Stephen H.; Meyer, Robert G. (Hoboken, New Jersey : Wiley, 2024)
'A very welcome new edition of the classic text for students and engineers covering the design of CMOS and bipolar analog integrated circuits. In addition to the well-established concepts, this 6th edition introduces a new super-source follower (SSF) circuit and its large-signal behavior, frequency response, stability, and noise properties. New material also introduces replica biasing; describes and analyzes two op amps with replica biasing; weighted zero-value time constants as a method to estimate the location of dominant zeros; pole-zero doublets including their effect on settling time and three examples of circuits that create doublets; the effect of feedback on pole-zero doublets; and MOS transistor noise performance, including a thorough treatment on thermally induced gate noise'--
Includes index.
Keywords: Linear integrated circuits; Metal oxide semiconductors; Bipolar transistors